Nano-Fertilizers and Nano-pesticides: Benevolence for Sustainable Agriculture - Ashu Chaudhary; Annu -; Mamta - (Nanochemistry Research)
The augmentation in population leads to increase food demand and respectively the utility of fertilizers and pesticides. Due to excess utility of chemical fertilizers and pesticides major environmental and health issues were observed. . Recent developments in Nano agrochemicals have attained interest of researchers due to its eco-friendly nature and cost-effectiveness. Here, in this article we reviewed the advantages of nano-tools being nanofertilizers and nanopesticides over the conventional mineral fertilizers and pesticides and the developments in nano-agrochemicals along with their applications in farming industries such as improving the crop production, minimizing the input and maximizing the output, solving agronomy problems being better food yield together with preservation. This review comprises latest impacts of nanotechnology in farming industries, nano-agrochemicals versus conventional agro-chemicals and nanomaterial as pesticides and fertilizers and sustainable development. Nano agrochemicals in form of Nanopesticides, Nanofertilizers, Nanobiofertilizers, Green Nanopesticides as well as Metallic nanopesticides are emerging as a new product for industry.